ANALYZING THE IMPACT OF THE COLLABORATION BETWEEN GRAB AND OVO TO THE CUSTOMER - Karisoh, Monica; Massie, James D. D.; Wangke, Shinta J. C. (Universitas Sam Ratulangi, 2019)
Abstract: Grab is one of the largest online transportation application in Indonesia and ovo is one of top financial application in Indonesia. Ovo is a technology-based payment services company which uses emerging financial technologies to provide new ways for customers to live their lives. This study aims to analyze how the impact of the collaboration between grab and ovo on customer satisfaction. This research employs a qualitative approach by conducting interviews with 15 sam ratulangi university students as the informants, which were chosen through purposive sampling. Findings of this research shows that the collaboration between grab and ovo has a good and positive impact in order to improve the customer satisfaction, and also the collaboration between grab and ovo are effective to the all customers who become an informant in this research. Grab and ovo should to keep improve their service and quality, so it can make the customers stay and their can have customers loyalty.Keywords: online transportation, grab, ovo, collaboration, customer satisfaction